CLOUD COMPUTING DEMYSTIFIED FOR ASPIRING PROFESSIONALS hone your skills in AWS, Azure, and Google cloud computing and boost your career as a cloud engineer - Santana, David (PACKT PUBLISHING LIMITED, 2022)
Gain in-depth knowledge of cloud computing concepts and apply them to accelerate your career in any cloud engineering role Key Features Get to grips with key cloud computing concepts, cloud service providers, and best practices Explore demonstrations for cloud computing models using real-world examples Adopt the self-paced learning strategy and get industry-ready for cloud engineering roles Purchase of the print or Kindle book includes a free eBook in the PDF format Book Description If you want to upskill yourself in cloud computing domains to thrive in the IT industry, then you've come to the right place. Cloud Computing Demystified for Aspiring Professionals helps you to master cloud computing essentials and important technologies offered by cloud service providers needed to succeed in a cloud-centric job role. This book begins with an overview of transformation from traditional to modern-day cloud computing infrastructure, and various types and models of cloud computing. You'll learn how to implement secure virtual networks, virtual machines, and data warehouse resources including data lake services used in big data analytics -- as well as when to use SQL and NoSQL databases and how to build microservices using multi-cloud Kubernetes services across AWS, Microsoft Azure, and Google Cloud. You'll also get step-by-step demonstrations of infrastructure, platform, and software cloud services and optimization recommendations derived from certified industry experts using hands-on tutorials, self-assessment questions, and real-world case studies. By the end of this book, you'll be ready to successfully implement cloud computing standardized concepts, services, and best practices in your workplace. What you will learn Gain insights into cloud computing essentials and public, private, hybrid, and multi-cloud deployment models Explore core cloud computing services such as IaaS, PaaS, and SaaS Discover major public cloud providers such as AWS, Microsoft, and Google Unlock the power of IaaS, PaaS, and SaaS with AWS, Azure, and GCP Create secure networks, containers, Kubernetes, compute, databases, and API services on cloud Develop industry-based cloud solutions using real-world examples Get recommendations on exam preparation for cloud accreditations Who this book is for The book is for aspiring cloud engineers, as well as college graduates, IT enthusiasts, and beginner-level cloud practitioners looking to get into cloud computing or transforming their career and upskilling themselves in a cloud engineering role in any industry. A basic understanding of networking, database development, and data analysis concepts and experience in programming languages such as Python and C# will help you get the most out of this book.